Does chronic obstructive pulmonary disease relate to poor prognosis in patients with lung cancer?: A meta-analysis. Issue 11 (March 2019) - Lin, Hefeng; Lu, Yunlong; Lin, Liya; Meng, Ke; Fan, Junqiang
Abstract: Background: Nowadays, there is growing recognition that chronic obstructive pulmonary disease (COPD) may have influence on lung cancer. However, coexisted COPD related to prognosis of lung cancer is still elusive. We conducted this meta-analysis to examine the association between COPD and 5-year overall survival (OS) and postoperative pulmonary complications of patients with lung cancer. Methods: A comprehensive computer-based online search was conducted using PubMed, Embase, Medline, and the Cochrane Library for articles published before September 30, 2017. We identified 29 eligible studies, which included 70, 111 patients in the related literature. Results: Twenty-two of the 29 studies provided hazard ratio for OS (1.18, 95% confidence interval: 1.11–1.25; P < .001), it suggested that the presence of COPD indicated poor survival for the patients with lung cancer. In subgroup analysis, the relationship between COPD and OS occurrence remained statistically prominent in the subgroups stratified by study designs, COPD diagnosis timing, lung cancer surgery, cancer stage, and origins of patients. The presence of COPD increased the risk of bronchopleural fistula, pneumonia, prolonged air leakage, and prolonged mechanical ventilation. Conclusions: The present meta-analysis suggested that coexisting COPD is associated with poor survival outcomes in patients with lung cancer and higher rates of postoperative pulmonary complications. Abstract : Supplemental Digital Content is available in the text